2012
DOI: 10.1007/s11033-012-1596-x
|View full text |Cite
|
Sign up to set email alerts
|

IL-1ra anti-inflammatory cytokine polymorphism is associated with risk of gastric cancer and chronic gastritis in a Brazilian population, but the TNF-β pro-inflammatory cytokine is not

Abstract: Genetic polymorphisms in genes that codify inflammatory cytokines have been associated with gastric carcinogenesis. This study evaluated polymorphisms IL-1RN VNTR and TNFB+252A/G in a population from Southeast Brazil with regard to the risk of chronic gastritis and gastric cancer and the presence of an association of gastric lesions with risk factors such as gender, age, smoking, drinking and Helicobacter pylori infection. In this case-control study, polymorphism at IL-1RN VNTR was investigated using the allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…Boccia et al [39] reported that the [50] , 2012, Brazil Zhang et al [56] , positive association between gastric cancer risk and high consumption of grilled/barbecued meat in Italy was more pronounced among SULT1A1 His/His carriers compared with Arg/Arg carriers. It is possible that low enzyme activity in the individuals with SULT1A1 His/His genotype may result in less detoxification of HCAs from high consumption of grilled/barbequed meat [39] .…”
Section: Effect Of Carcinogen Metabolism-related Genetic Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…Boccia et al [39] reported that the [50] , 2012, Brazil Zhang et al [56] , positive association between gastric cancer risk and high consumption of grilled/barbecued meat in Italy was more pronounced among SULT1A1 His/His carriers compared with Arg/Arg carriers. It is possible that low enzyme activity in the individuals with SULT1A1 His/His genotype may result in less detoxification of HCAs from high consumption of grilled/barbequed meat [39] .…”
Section: Effect Of Carcinogen Metabolism-related Genetic Polymorphismmentioning
confidence: 99%
“…In those who consume fewer soybeans, IL-10 genetic variants may allow infection with more virulent H. pylori strains and increase gastric inflammation [49] . Oliveira et al [50] investigated the modifying effects of alcohol on the association between genetic polymorphisms anti-or pro-inflammatory cytokines and gastric cancer risk in Southeast Brazilians but found no significant interactions.…”
Section: Effect Of Carcinogen Metabolism-related Genetic Polymorphismmentioning
confidence: 99%
“…They are located within the coding and promoter regions of genes, and thereby affect gene function. Several SNPs are associated with susceptibility to infectious disease (Lu et al, 2005;Reale et al, 2011;Oliveira et al, 2012;Christaki and Giamarellos-Bourboulis, 2014). Although their functional role remains to be established, several SNPs are believed to affect the production of cytokines (Tsezou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The first step was a case-control study on chronic gastritis (CG) and gastric cancer (GC), in which a total of 723 peripheral blood DNA samples from a previous study [26], which had been stored in our laboratory and genotyped for cytokine polymorphisms, were assessed. The first case group comprised 276 patients (142 men and 134 women) with a histopathologically confirmed diagnosis of chronic gastritis according to the Sidney System [27] and a mean age of 53.7±14.41 years (range 19-86 years).…”
Section: Subjects and Samplesmentioning
confidence: 99%